PENGARUH BUDAYA TOLERANSI KEKUASAAN TERHADAP PERSEPSI KARIR BIROKRATIK DAN PROFESIONAL (Studi Empirik pada Profesi Perawat RS. Islam Sultan Agung Semarang) (Proceeding Fakultas Ekonomi, 2014)
Organization culture is collection of positive value that is useful for organization in order to influence behavior. Authority tolerance culture is part of culture concept founded by Hofstade (1994). As high as authority to culture, means they are willing to accept the authority to culture difference in an organization. Career perception is perception as long as working (Asthur, et al, 1989. The aim of this research  are to analyze and to prove whether tolerant culture influence bureaucratic and professional career perception. Method of this research uses purposive sampling method with 89 female nurse as samples and also uses double regression analysis. Result of this research shows that authority tolerance culture has positive influence towards bureaucratic to career perception and professional career perception. It means that as high as authority tolerance culture will determine life someone’s career choice, even though still in perception form. Next, this perception will influence someone’s behavior in acting to do pioneering career. Keywords : Authority tolerance culture, Bureaucratic Career Perception, Professional Career Perception.